Revisiting Key Sedimentary Archives Yields Evidence Of A Rapid Onset Of Mining In The Mid‐13th Century At The Great Copper Mountain, Falun, Sweden. (14th July 2015) - Bindler, R.; Rydberg, J.
Abstract : Mining in Falun, Sweden, was first mentioned in a deed fromad 1288, but previous studies of peat and lake sediments inferred that mining began during the fifth to eighth centuries. In order to reassess these findings, we performed new geochemical analyses on new samples from three key sites: Tisksjöbergets myr, a buried mire alongside the mine; Tisken, a small lake in Falun; and Runn, the main recipient for waters draining through Falun. At Tisksjöbergets myr, the peat contains up to 6% copper, giving it the characteristics of a cupriferous bog. Hence, this record is not useful for tracing early mining. The sediments of Tisken—upon which many of the old interpretations have relied—contain numerous cut wood fragments, and two of those gave young and reversed radiocarbon dates (19th and 16th centuries for 192 and 187 cm, respectively). This indicates that the sediment was derived from infilling and, thus, has little value as a historical record. Runn's sediment—the only reliable record—provides clear evidence of a rapid onset of large‐scale mining from c.ad 1245, with abrupt increases in ore‐related elements—for example, a 34‐fold increase in copper—this increase is consistent with the mid‐13th century burial of the mire at Tisksjöberget.